DIGITAL INNOVATION IN RURAL FINANCIAL INSTITUTIONS: CLOUD BASED SAAS ADOPTION IN KRISHI PATPEDHI SOCIETIES - Patil, Sidagouda Basagouda; Kulkarni, Mukund (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Small banks and credit unions in rural areas often have trouble with limited IT resources and security issues. This paper examines a cloud-based Software-as-a-Service (SaaS) solution to enhance resource optimization and bolster data security for Primary Krishi Patpedhi Societies (PKPS) in rural India. A quantitative survey involving 200 respondents from 20 PKPS units was executed to evaluate existing practices and preparedness for cloud adoption. The results show that 90% of those who answered see an urgent need for software in operation, but 70% still use manual processes. More than 75% of people are unhappy with the systems they have now, but just as many think that cloud solutions are helpful. Only 30% of people currently use cloud tools, but 80% would be willing to use them if they got the right help and training. A prototype cloud-based platform was built using a web app (PHP) and a mobile app (Flutter) with MySQL/SQLite databases. It showed off features for centralized account management and safe transactions. The proposed SaaS model uses encryption and access controls to make security concerns less of a problem. The integrated solution makes things a lot more efficient (with concurrent processing and automated workflows) and makes sure that data protection rules are followed. This study finds that cloud-based solutions can improve resource optimization and security for rural financial institutions in a cost-effective way, as long as the technology is deployed with the right infrastructure and training.